Apoptotic-related signalling pathways in mcf-7 cells treated with ethyl acetate extract of dillenia suffruticosa, and isolation of its major compounds - Yin, Sim Tor (2015)
Breast cancer is the most prevalent cancer among women worldwide. The trend for breast cancer treatment has shifted towards the use of natural product such as herbal medicine as an alternative and complementary medicine. Dillenia suffruticosa (Griff) Martelli that belongs to the family Dilleniaceae has been traditionally used to treat cancerous growth. In this study, the anti-cancer activity of ethyl acetate extract of D. suffruticosa (EADs) root was examined on breast cancer cells, MCF-7. EADs was prepared from the root of D. suffruticosa by using sequential solvent extraction. MTT assay was used to determine the cytotoxicity of EADs, which was demonstrated to be dose- and time-dependent, with IC50 of 39 ± 3.6 µg/mL at 72 hours. Flow cytometry cell cycle analysis displayed that EADs induced non-phase specific cell cycle arrest. EADs induced mainly apoptosis in MCF-7 cells in Annexin-FITC/PI analysis. The use of general caspase-inhibitor Z-VAD-FMK indicated that EADs-induced apoptosis was caspase-independent. EADs was found to promote oxidative stress that will lead to cell death because the pre-treatment with antioxidants α-tocopherol and ascorbic acid significantly reduced the cytotoxicity of the extract (P<0.05). DCFH-DA assay revealed that treatment with EADs attenuated the generation of intracellular ROS. The use of JC-1 dye reflected that EADs caused disruption in the mitochondrial membrane potential. Up-regulation of p53 and p21, is believed has led to EADs-induced nonphase specific cell cycle arrest (P<0.05). Elevation of Bax/Bcl-2 ratio and the depolarization of mitochondrial membrane potential indicated that EADs-induced apoptosis was mitochondrial-dependent.The expression of oxidative stress–related proteins AKT, p-AKT, ERK, and p-ERK was downregulated with upregulation of JNK and p-JNK suggesting that induction of apoptosis by EADs is mediated by inhibition of AKT and ERK, and activation of JNK. The major compounds of EADs were then isolated using column chromatography and elucidated using nuclear magnetic resonance analysis producing a total of 6 compounds. The cytotoxicity of the isolated compound was determined using MTT assay. Gallic acid was found to be most cytotoxic against MCF-7 cell line compared to others, with IC50 of 36 ± 1.7µg/mL (P<0.05). In summary, EADs induced cell cycle arrest, oxidative stress and apoptosis in MCF-7 cells Thus, EADs has the potential to be developed as an anti-cancer agent against breast cancer.